2015
DOI: 10.5387/fms.2014-30
|View full text |Cite
|
Sign up to set email alerts
|

Brain Hypothermia Therapy for Neonatal Hypoxic-Ischemic Encephalopathy With a Severely Elevated Serum Creatine Kinase Level

Abstract: : Several studies have shown that brain hypothermia therapy (BHT) after neonatal hypoxic -ischemic encephalopathy (HIE) can improve neurodevelopmental outcomes. However, there have been no reports of the neurodevelopmental outcomes for the infant with a serum creatine kinase (CK) level above 20,000 IU/L in association with neonatal HIE. We report a female infant with a very high serum CK level (26,428 IU/L) associated with neonatal asphyxia. We diagnosed this infant with moderate HIE, and BHT was achieved by h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(8 reference statements)
0
1
1
Order By: Relevance
“… 9 , 29 , 30 , 36 There was a case report about an infant that had a very high CK-BB >26.000 IU/L and that developed some neurodevelopmental delay in spite of receiving brain hypothermic therapy. 40 Against our study, Huang et al found a nonsignificant trend for the urinary L/C ratio to increase with the severity of the HIE. 28 …”
Section: Discussioncontrasting
confidence: 65%
“… 9 , 29 , 30 , 36 There was a case report about an infant that had a very high CK-BB >26.000 IU/L and that developed some neurodevelopmental delay in spite of receiving brain hypothermic therapy. 40 Against our study, Huang et al found a nonsignificant trend for the urinary L/C ratio to increase with the severity of the HIE. 28 …”
Section: Discussioncontrasting
confidence: 65%
“…Further, as postnatal blood gas is easily corrected by active resuscitation, it may not be possible to correctly evaluate the hypoxemic condition before or soon after birth. Although the elevation of deviation enzymes such as lactate dehydrogenase (LDH), and creatine kinase (CK) has been widely recognized as useful in identifying damaged tissue, 6,7 there are few reports focusing on various blood count indicators related to the severity of fetal distress or neonatal asphyxia. Currently, blood count is frequently used in the diagnosis and followup of blood diseases and infectious diseases, even in neonatal infants.…”
Section: Introductionmentioning
confidence: 99%